Un moindre mal pour les travailleuses? La Commission du salaire minimum des femmes du Québec, 1925-1937 - Leroux, Éric (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 2003)
Abstract Over the last few years, the activities of minimum wage commissions in the western provinces and in Ontario have been the subject of several historical studies. Inspired by these projects, this paper examines the work of the Quebec Women's Minimum Wage Commission, from its inception in 1925 to its dismantling in 1937. After giving reasons which forced the Quebec government to legislate on this issue, the author presents the position of international and catholic unions on women in the work force. In his analysis of the operating mode of the commission and, more precisely, his critical evaluation of its mechanism for enforcing the law, the author concludes that as with the other commissions across Canada, the Quebec Women's Minimum Wage Commission would not have allowed wage increases for women. In a socio-economic context where women on average made half of the salary of men, the decision to use the minimum wage as a tool to fight the abuse of the capitalist system had the major consequence of keeping salaries low. In fact, the low rate of the minimum wage agreed to by the commission upheld the principle of pay inequity by gender, thus reflecting the dominant ideology of the era during which the work of women was considered marginal.